Imaging characteristics of metastatic nodes and outcomes by HPV status in head and neck cancers. (7th September 2015) - Fujita, Akifumi; Buch, Karen; Truong, Minh Tam; Qureshi, Muhammad M.; Mercier, Gustavo; Jalisi, Scharukh; Sugimoto, Hideharu; Sakai, Osamu
Abstract : Objectives/Hypothesis: Although several imaging characteristics of human papillomavirus (HPV)‐related head and neck squamous cell carcinoma (HNSCC) have been reported, imaging features of nodal metastasis and influence to outcomes have not been well studied thus far. The purpose of the study was to investigate the imaging characteristics of nodal metastasis by HPV status in HNSCC and to clarify whether those findings influence the outcomes. Study Design: Retrospective review. Methods: Computed tomography and magnetic resonance imaging for initial staging on 139 patients of HNSCC with known HPV status were retrospectively reviewed. We investigated imaging characteristics of the nodal metastasis including the presence of extracapsular spread (ECS), and also investigated the influence of nodal metastasis characteristics to outcomes by HPV status. Two‐year actuarial control and survival rates were estimated using the Kaplan‐Meier product‐limit method ( P < 0.05). Results: Eighty‐eight patients with nodal metastasis were identified and outcome information was available for 78 patients. Nodal metastasis was significantly more common in HPV‐positive patients compared to HPV‐negative patients (75% vs. 54%, P = 0.009). HPV‐positive patients showed a higher prevalence of ECS compared to HPV‐negative patients (77% vs. 56%, P = 0.041). The prevalence of disease recurrence was more common in HPV‐negative patients (67% vs. 13%, P < 0.0001), and it was independent of the presence of ECS in nodal metastasis. Conclusions: Nodal metastases were significantly more common in HPV‐positive HNSCC, whereas the prevalence of disease recurrence was greater in HPV‐negative HNSCC. Although ECS was noted in the majority of the HPV‐positive patients with nodal metastasis, rates of recurrence were lower compared to HPV‐negative patients. Level of Evidence: 4. Laryngoscope, 126:392–398, 2016